A potential role for immigrant reproductive behavior in the outcome of population augmentations. (11th February 2019) - Mensch, E. L.; Kronenberger, J. A.; Broder, E. D.; Fitzpatrick, S. W.; Funk, W. C.; Angeloni, L. M.
Abstract: Augmenting wild populations with translocated individuals is a powerful conservation tool to achieve genetic rescue, but little is known about the role mating behavior plays in the success of augmentation efforts. We studied the behavior of male Trinidadian guppies Poecilia reticulata introduced into experimental mesocosm populations and assessed whether mating behavior influenced reproductive success. A previously published analysis of the same experiment found that populations from the Quare River had higher immigrant reproductive success than populations from the Marianne River, contributing to higher population fitness following augmentation. However, the reason for high immigrant reproductive success remained unclear. Our behavioral observations of a subset of those populations revealed that immigrant males from Quare (but not Marianne) performed more sexual displays and forced copulations and had marginally higher reproductive success than resident males. These results, combined with significant differences in reproductive success and population fitness reported in the previous study, suggest that mating behavior may have improved the outcome of augmentation by increasing genetic admixture. We urge wildlife managers and researchers to consider mating behavior as a factor influencing augmentation success. Abstract : Augmenting wild populations with translocated individuals is a powerful conservation tool to achieve genetic rescue, but little is known about the role mating behavior plays in the success of augmentation efforts. We assessed whether mating behavior influenced reproductive success in the Trinidadian guppy Poecilia reticulata and found results to suggest that mating behavior may have improved the outcome of augmentation by increasing genetic admixture. We urge wildlife managers and researchers to consider mating behavior as a factor influencing augmentation success.